Effective techniques for restoration of heritage masonry. (16th August 2011) - Korany, Yasser
Structural restoration of heritage masonry buildings is a serious challenge. Meeting the requirements of current building codes is not sufficient to preserve the historic character of heritage buildings. The selected technique must be consistent with aesthetics, function, and the requirements of strength, ductility, and stiffness. This paper provides an overview of the traditional and recent techniques that have been proven to be effective in restoring heritage masonry structures. The special requirements for restoration of heritage structures and the main non-destructive evaluation methods that could be used to assess their structural condition are discussed.